Theatre, performance and technology the development and transformation of scenography - Baugh, Christopher (Basingstoke, Hampshire Palgrave Macmillan, 2013)
Throughout history, scenography has played a significant role in theatre, always drawing upon the latest technologies of manufacture and control. In the twenty-first century, it is fast becoming an artistic practice in its own right, engaging with audiences in varied ways. Christopher Baugh considers how change in scenographic identity has impacted upon the place and meaning of performance over the past 300 years. Thoroughly revised and updated, the second edition discusses: moving light technologies; the Internet as a platform of performance; urban scenography; scenography's role in the creation of memory; the development of scenography as a collaborative practice.
Performing Great Exhibitions: A Nineteenth-Century Speciality -- Rejection of the Past: A Modern Mode of Thought -- The Scene as Machine, 1: Scenography as a Machine for Performance -- The Scene as Machine, 2: Constructing and Building the Scene as Machine -- The Scene as Machine, 3: The Kinetic Stage Machines of Josef Svoboda -- The Century of Light, 1: Diffused and Living Light -- The Century of Light, 2: Light Beams and Images -- The Scene as the Architecture of Performance -- Some Rejections of Technology in Theatre and Performance -- New Technologies and Shifting Paradigms -- Scenography as Dramaturgy of Performance.
Previous edition: 2005.
Includes bibliographical references and index.
Keywords: Theaters -- Stage-setting and scenery; Theaters -- Stage-setting and scenery -- Technological innovations